The Effectiveness of Buckroyd’s Group-Based Therapeutic Approach on Increasing Self-Esteem and Improving Eating Attitude of Obese -20 to 30-Year-Old Females in Esfahan - Fariba Hosseini; Yousef Gorgi; Afsaneh Javadzadeh (Journal of Education and Community Health)
Background and Objectives: Obesity has been increasing around the world and this phenomenon is creating many physical and psychological problems. Hence, this study considered the effectiveness of Buckroyd’s group-based therapeutic approach on increasing self-esteem and improving eating attitude of obese 20- to 30-year-old females in Esfahan. Materials and Methods: This study was semi-experimental, statistical society of which involved all obese females referred to Sepahan Salamat Clinic in Esfahan, during year 2014. Overall, 30 over-weight females, who had a Body Mass Index (BMI) between 25 and 35, a minimum education of diploma, and age of 20 to 30 years old were selected purposefully and divided randomly to two equal groups. Buckroyd’s therapy was performed in sixteen sessions and each session lasted two hours twice per week. Research measurements included body mass index, demographic form, self-esteem and eating attitude questionnaires. Variance analysis and frequency measurement were performed with the SPSS-20 software and were used for confirming the hypothesis. Results: Results showed that Buckroyd’s group therapy increased self-esteem (P <0.001), but didn’t improve eating attitude (P >0.05). Conclusions: The findings showed that Buckroyd’s therapy approach can be used for increasing self-esteem but cannot be used for improving eating attitude of obese females.